2001
DOI: 10.1002/1521-4095(200103)13:6<433::aid-adma433>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Photonic Bandgaps in Disordered Inverse-Opal Photonic Crystals

Abstract: Three‐dimensional photonic crystals with full bandgaps at optical wavelengths can be fabricated with inverse‐opal techniques. We have shown that the bandgap is extremely sensitive to the presence of geometric disorder in the crystals (see Figure). The bandgap closes completely with a disorder strength as small as under two percent of the lattice constant. This fragility persists even at very high refractive index contrasts and is attributed to the creation of a bandgap at high frequency bands (8–9 bands) in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 12 publications
0
30
0
Order By: Relevance
“…Band gaps between lower lying bands, such as those that occur in the case of the diamond structure, are predicted to be much less sensitive to disorder [5]. Li et al proposed the FCC arrangement of nonspherical dimer building blocks to mimic the diamond structure, which has two dielectric spheres per lattice point [6].…”
Section: Introductionmentioning
confidence: 99%
“…Band gaps between lower lying bands, such as those that occur in the case of the diamond structure, are predicted to be much less sensitive to disorder [5]. Li et al proposed the FCC arrangement of nonspherical dimer building blocks to mimic the diamond structure, which has two dielectric spheres per lattice point [6].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of unwanted intrinsic defects such as cracks, vacancies, dislocations, and grain boundaries in colloidal crystals degrades the optical quality of a colloidal crystal template, thus largely eliminating the PBG behavior of the resultant 3D PhC. [101][102][103] Fortunately, theoretical studies [104][105][106][107] and recent experimental studies have shown that using an appropriate self-assembly technique [47,49,[108][109][110][111] and highly uniform colloidal spheres, [47,49,108] the formation of unwanted intrinsic defects in self-assembled colloidal crystals can be substantially avoided.…”
Section: Discussionmentioning
confidence: 99%
“…These materials exhibit an interconnected 3D network with high surface area, since the constituent spheres of the colloidal crystals have been removed. Inverse opals have attracted strong interest in photonic crystal research, due to their full photonic band gap, [64,65] and are also promising but unexplored materials for phononic experiments.…”
Section: Vertical Lifting Deposition and Colloidal Crystalsmentioning
confidence: 99%